The social economy of new rural reconstruction - Jia'en, Pan; Jie, Du (China Journal of Social Work, 2011)
This paper employs the concept of ‘social economy’ to reflect on the authors' experiences in rural reconstruction efforts in Mainland China, including work on peasant cooperatives and community-supported agriculture. In practice, the social and the economic can never be clearly separated. Economic problems, which may superficially appear to be independent, are in fact over-determined by all kinds of social and cultural factors, so a holistic perspective of ‘social economy’ is needed to re-embed the economic into its social context. Such a perspective can help expand the space of our practice and reflection thereon, in particular helping practitioners to understand the difficulties encountered in rural reconstruction.
Cultural Studies
Keywords: China; new rural reconstruction; perspective; social economy

Neoliberalism as a state-centric class project: The Italian case - Briziarelli, Marco (Continuum: Journal of Media & Cultural Studies, 2011)
This essay sheds light on the neoliberal aspects of the Italian political-economic system exemplified in the relationship between capital, state and media. The main argument is that the specific marriage between neoliberalism and neocorporatism that characterizes Italy reveals a distinctive characteristic of neoliberalism: a class project relying heavily on the state. As Polanyi has suggested through the concept of 'embeddedness', capitalism has consistently developed through the double movement of preaching the independence of the free market from the state and requiring the state's protectionist interventions. After describing this state-centric framework to interpret neoliberalism, in the second part of the paper, I consider the political-economic history of Italy's recent decades, paying particular attention to the media system. I will examine the 'communicative performance' of neoliberalism in Berlusconi's discourses and concrete political decisions taken in the name of neoliberalism. The articulated relationship between media and politics reveals the continuous attempts by the advocates of neoliberalism to seize the state, not to reduce its intervention but in fact to manipulate the market.
Communication Studies; Media Studies; Cultural Studies
Keywords: Italy; economic indicators; essays; mass media audiences; neoliberalism; political economic analysis

Local Food: A Social Movement? - Starr, Amory (Cultural Studies/Critical Methodologies, 2010)
This article analyzes the development of “local food” institutions from a social movements perspective. Over the last decade, institutions that “shorten the links” between producer and consumer have developed through a diverse collaboration of many social sectors (farmers, agronomic experts, retailers, chefs, food writers, and several distinct consumer sectors). Some agronomists and rural sociologists critical of the globalization and industrialization of agriculture have recognized this development as heralding Polanyian “reembedding” of market exchanges in social relations. This article analyzes whether and how local food is a social movement, using new social movement theory as an analytic framework.
Sociology; Cultural Studies
Keywords: community-based economics; local food; local foods; localism; organic food; organic foods; social change; social movements; social psychology

Economics and the Space of Modernity: - Escobar, Arturo (Cultural Studies, 2005)
This text was the original second chapter of the author's doctoral dissertation (Escobar 1987); this chapter was never included in the book that eventually grew from the dissertation (Escobar 1995). Although the chapter's contribution to debates on the economy are largely synthetic and certainly not original, the author wanted to publish it for a number of reasons. First, the alleged triumph of neo-liberal ideologies and the increase in depth and scope of market cultures at present make even more important the task of cultural analysis of economics and the economy. This paper was an effort in this direction, particularly to mapping the genealogies of what in the paper is called ‘the Western economy’. Second, there have been some recent claims that the cultural analysis of economics and the economy has hardly been broached. References to Polanyi's foundational role in this respect are, of course, de rigueur, but one only needs to point at the pioneering work of Stephen Gudeman since the 1980s to dispute this claim. Third, the same cultural analysis is experiencing a much needed surge, with several groups today fully engaged with it from various – some times overlapping – perspectives. Finally, the impetus for this piece also comes from the creative efforts by a number of social movements in the world – such as some of the autonomistas in Argentina – to go even beyond ‘rethinking’ the economy to propose that what is needed is a new invention altogether.
Anthropology; Cultural Studies
Keywords: anthropology of modernity; cultural studies; cultures of economy; economic history; economics; genealogy; modernity; resistance; social history; third world

The Specter of the 1930s in Asian Nation-Building: Global Fascism, Colonial Biopolitics, and the Origins of Modern Asia - Lee, Alex Taek-Gwang (Back to the ‘30s? : Recurring Crises of Capitalism, Liberalism, and Democracy, 2020)
An analysis of the connection between fascism and biopolitics in modernizing East Asia reveals that fascism served as colonial biopolitics, and was not historically specificity to Europe, though the rise of fascism was central to European colonialism and its technology of governance. As the last stage of capitalism, imperialism came with an expansion of social engineering in colonial countries, forcing colonized peoples to be “civilized.” I challenge the understanding of European fascism, arguing that fascism is inseparable from colonial biopolitics by analyzing non-European experiences in the 1930s. East Asia was then a site in which fascism, premised on building a utopian nation-state, played a pivotal role in encouraging people to insist upon political and economic autonomy in order to compete with Europe. The Manchurian Empire (滿州帝國) was an attempt to realize this utopian idea of fascism. Finally, I argue that these fascist experiences remain influential in the region and constitute a mirror image of European modernity.
Cultural Studies
Keywords: Japanese Fascism and Imperialism; Japanese colonialism; Manchukuo; history and politics; biopolitics of colonialism; fascism; nationalism and nation-building in East Asia